Place-based and participative approaches: reflections for policy design in rural development - Kim Pollermann; Lynn-Livia Fynn (Proceedings 13th World Congress of the RSAI: Smart Regions - Opportunities for sustainable development in the digital era, virtual conference May 25-28, 2021, 2021)
Across the European Union, the so-called "Community-Led Local Development" (CLLD) is a well-established policy instrument. It began with LEADER in rural areas over 30 years ago and now comprises over 3000 Local Action Groups (LAGs) across the continent. LEADER is a place-based and participatory approach where a Local Action Group composed of stakeholders from local government, civil society and economy steers the implementation of its local development strategy. LAGs each have a budget at their disposal to support project implementation within the EU funding period (time for implementation is around five years). A set of LEADER principles describes the characteristics of LEADER: territorial approach, bottom-up, public-private partnerships, integrated and multi-sectoral approach, innovation, cooperation with other regions and networking. The aim of this contribution is to discuss different possibilities for policy design of LEADER implementation regarding different steering options. To examine the performance of LEADER, we utilise results from the 2014-2020 funding period, specifically data from 115 LAGs from four federal states in Germany. Main material was collected by three surveys using written questionnaires (mainly executed as online surveys: LAG member survey n=1999, LAG management survey n=114, survey of beneficiaries: n=1079). The results are related to single variables of LEADER implementation and their impact on the performance of LEADER. Due to complex relations of different aspects, we mainly elaborate findings on simplified output indicators. Regarding a suitable policy design, the results offer several insights: in the context of spatial delimitation, results show that a suitable region design/delimitation is not dependent on the population size of the various LEADER regions. To foster a higher share of innovative projects, it is adjuvant to establish a suitable staff capacity in LAG managements. This supports a policy recommendation to predefine minimum targets for staff capacity as a prior condition for funding the LAGs, as this shows be an important factor to support innovation and participation of local actors.
Keywords: R58; 330; Community-Led Local Development (CLLD); LEADER; participation; rural development